Student and Staff Views on Inclusion and Inclusive Education in a Global South and a Global North Higher Education Institution - Acquilina Wafula Nawire; Sally Musungu; Vasiliki Kioupi; Felister Nzuve; George Giannopoulos (Education Sciences)
This article presents views and experiences of staff, and learners from two Higher Education Institutions (HEIs)—the University of Nairobi in Kenya and UCL in the UK—on their intuitional structures, support, and education mechanisms related to disability, international and refugee status. Inclusive education is a complex subject and often the focus is particularly placed on learners with disabilities, but this study explored several layers of diversity. The objective of this study was to investigate the views and experiences of students and staff on policies and practices of inclusion and inclusive education using two case studies, one in each university. Data were collected through surveys and interviews. Results are presented in the following areas: (1) capacity building for staff; (2) support and reporting services for all; (3) class sizes; and (4) modes of course delivery. Findings reveal that implementation of inclusion and inclusive education is still a challenge for both HEIs. The gaps identified can be used as a reference point for action. Inclusion and inclusive education are necessary to ensure the needs of every learner and staff are met. The article is structured into five sections: a brief description of inclusive education in the two HEIs, methodology, results, discussion, and conclusion.